Edouard Glissant e o legado de William Faulkner - Figueiredo, Eurídice (Centro de Estudios de Teoría y Crítica Literaria, IdIHCS - CONICET. Facultad de Humanidades y Ciencias de la Educación. UNLP, 2011)
This paper aims to analyze the intertextual links between Édouard Glissant and William Faulkner in two works: the essay Faulkner, Mississippi [1996] and the novel Sartorius [1999]. In the first one, the author highlights issues already present in his own novelistic work: genealogy, the relationship with the plantation, métissage, the [il]legitimacy of rights regarding land ownership, opacity. In the novel, he draws the genealogical line of a character belonging to an imaginary African ethnic group and finishing up on the plantations of the American South; at the same time, he presents the Sartoris' family tree. I intend to show how Glissant's literary project establishes a dialogue with Faulkner's work, exploring and inventorying the same issues around the diaspora of peoples and their insertion into the plantation regime, whether in the South of the United States or on the Caribbean Islands. In the works of both authors one can perceive the same tragic fate haunting the characters, leading them to madness, suffering and death